Dinamika Konflik Petani dan Peternak di Kecamatan Nisam Kabupaten Aceh Utara - Yunanda, Rizki; Fasya, Teuku Kemal; Nasution, Abdullah Akhyar; Sartika, Ayu; Ningsih, Sri Wahyu (Sociology Department Of Syiah Kuala University, 2024)
This study aims to identify the root causes, forms of conflict, and solutions to farmers' resistance against free-grazing livestock practices in Nisam Subdistrict, North Aceh Regency. The conflict is triggered by crop damage caused by free-roaming livestock, differing interpretations of regulations, and land-use changes. This research employs a qualitative approach with an ethnographic method and uses James Scott's resistance theory as the analytical framework. Data were collected through non-participant observation, in-depth interviews, and document analysis. The findings reveal that the conflict significantly impacts agricultural productivity and social relations between farmers and livestock owners. Proposed solutions include restricting grazing areas, improving fences, providing compensation to farmers, and strengthening the role of the government and village officials in enforcing regulations, providing facilities, and monitoring. These findings underscore the importance of stakeholder collaboration in fostering harmonious relations and supporting the sustainability of the agricultural sector.AbstrakPenelitian ini bertujuan mengidentifikasi akar masalah, bentuk konflik, dan solusi atas resistensi petani terhadap praktik peternakan lepas liar di Kecamatan Nisam, Kabupaten Aceh Utara. Konflik ini dipicu oleh kerusakan tanaman akibat ternak lepas, perbedaan pemahaman regulasi, serta alih fungsi lahan. Penelitian ini mengunakan pendekatan kualitatif dengan metode etnografi dan menggunakan teori resistensi James Scott sebagaia kerangka analisis. Data diperoleh melalui observasi non-partisipan, wawancara mendalam, dan analisis dokumen. Hasil penelitian menunjukkan bahwa konflik berdampak besar terhadap produktivitas pertanian dan hubungan antara petani serta peternak. Solusi yang diusulkan meliputi pembatasan area ternak, perbaikan pagar, pemberian kompensasi kepada petani, dan penguatan peran pemerintah serta aparatur desa dalam penegakan peraturan, penyediaan fasilitas, dan pengawasan. Temuan ini menegaskan pentingnya kolaborasi antara pemangku kepentingan untuk menciptakan hubungan harmonis dan mendukung keberlanjutan sektor pertanian.